The Influence of Municipal Minimum Wage, Education, GRDP, and Business Unit Numbers on the Absorption of Manufacturing Work Force in Central Java - Gaiandra Prana Palguna; Devanto Shasta Pratomo (Journal of Development Economic and Social Studies, 2026)
The manufacturing industry plays an important role in the economy by generating value added and creating employment opportunities. In Central Java Province, the manufacturing sector is the largest contributor to Gross Regional Domestic Product (GRDP), yet its employment absorption remains lower than that of the agricultural sector. This condition indicates a gap between the economic contribution of the manufacturing sector and its ability to create employment opportunities. This study aims to analyze the effects of the Regency/Municipality Minimum Wage (RMW), education level, manufacturing sector GRDP, and the number of business units on manufacturing employment absorption in Central Java Province. This study uses panel data from 35 regencies/municipalities during the 2017–2022 period, analyzed using the Fixed Effect Model (FEM). The results show that the Regency/Municipality Minimum Wage has a negative and significant effect on employment absorption, while education level has a positive but insignificant effect. Meanwhile, manufacturing sector GRDP and the number of business units have positive and significant effects on employment absorption. These findings imply that the government should establish balanced wage policies and encourage industrial growth through increased production, investment, and business development to expand employment opportunities in the manufacturing sector of Central Java.